Turkey’s dissonant engagement with modernity - Bazzi, Emad (Intellectual Discourse, 2012)
Turkey is the first Muslim country to engage with modernity as an integral phenomenon; its cultural and intellectual components being pre-requisites for its political project, and embodied in democracy. This paradigm, which was adopted by Ataturk and his secularist elites failed for several reasons. A markedly different approach was put forward by the Justice and Development Party which came to power in 2002 in which the modern political system was posited on conservative religious values in an attempt to come to terms with modernity and provide a model for the Muslim world. This latter undertaking shows signs of dissonance, ambiguity and uncertainty. It also does not conform to the paradigm of multiple modernities through which a country achieves progress and development without submitting to the intellectual discourse of modernity or its political project. The approach adopted by the Justice and Development Party seems to fall within what is termed Post-Islamism in which a fusion is made between Islam and freedom, sharī‘ah and human rights, and piety and women’s empowerment. This article is devoted to the exploration of the above themes.